2023
DOI: 10.2147/idr.s416860
|View full text |Cite
|
Sign up to set email alerts
|

The New Changes of Epidemiology, Etiology, and Clinical Characteristics of Pyogenic Liver Abscesses: A Retrospective Study in a Hospital in Northern China

Abstract: Purpose To investigate the epidemiology, etiology, and clinical characteristics of patients with pyogenic liver abscesses (PLA) and provide guidance for clinical treatments. Patients and Methods A retrospective study was performed on a cohort of 402 hospitalized patients diagnosed with PLAs at the Affiliated Hospital of Chengde Medical College between January 2016 and December 2021. Patient demographics, drug sensitivity profiles, and microbiological culture results of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 39 publications
1
1
0
Order By: Relevance
“…The results demonstrated that patients with GFPLA had worse liver function, more severe in ammatory responses, and a higher in-hospital mortality rate than patients with non-GFPLA, in line with previous studies indicating that GFPLA has more severe clinical characteristics [6, 8, [22][23][24]. Investigations of risk factors associated with GFPLA can help clarify the underlying pathological mechanisms of the greater disease severity in patients with GFPLA.…”
Section: Discussionsupporting
confidence: 87%
“…The results demonstrated that patients with GFPLA had worse liver function, more severe in ammatory responses, and a higher in-hospital mortality rate than patients with non-GFPLA, in line with previous studies indicating that GFPLA has more severe clinical characteristics [6, 8, [22][23][24]. Investigations of risk factors associated with GFPLA can help clarify the underlying pathological mechanisms of the greater disease severity in patients with GFPLA.…”
Section: Discussionsupporting
confidence: 87%
“…However, if the infection is not effectively managed, it can progress to disseminated infection, sepsis, and potentially death, especially in individuals with type 2 diabetes mellitus (T2DM). 5,7,8 PLA patients with DM tend to experience more severe symptoms compared to PLA patients without DM. 9,10 Over 140 million Chinese adults were estimated to have diabetes in 2021, and this number is projected to increase to over 174 million by 2045.…”
Section: Introductionmentioning
confidence: 99%